UML Based Ontology for the Extraction of Historical Geographic Information - Piotr KOSIUCZENKO (Communications of International Proceedings, 2020)
Processing textual information in large files is time consuming and error prone. Investigating past and historical data concerning geography and economics can be facilitated a lot when the data is stored in a data base or has a proper form. There was a lot of research concerning the transformation of textual data to an ontology in a methodical way. In this paper, a method is presented for the extraction of geographic and economic information from a historic Lexicon. The method is based on software engineering techniques and follows an iterative cycle. It results in a well-defined ontology specified using UML class diagrams which can be queried using Object Constraint Language. An evaluation of the model is discussed. This research may help in assessing regional development, qualitative and structural changes in the regional economy, assessing ownership, infrastructure and living standard transformation.
Keywords: Software Engineering; Geographic Information Systems; Ontology; UML.